Introduction of a new electronic medical weekend handover at Tunbridge Wells Hospital. Issue 1 (5th March 2015) - Vithlani, Rohan
Abstract: Effective handover between shifts is vital to protect patient safety and assist doctors with clinical governance. Poor quality, or inadequate handover can lead to serious harm for both patients and doctors. The weekend medical handover system among junior doctors at Tunbridge Wells Hospital in Pembury, UK was cumbersome, inadequate and poor, restricting the ability to provide good patient care. 78.6% of doctors felt that the introduction of an electronic weekend handover system would address the issues in order to improve communication between the medical teams and thus improve patient care. A five week trial of an excel based electronic weekend handover system was conducted. 87.5% of the doctors surveyed felt that the new electronic weekend handover was better or significantly better than the old paper based handover system. The effectiveness rating of the weekend medical handover, with 1 (least effective) - 10 (most effective), rose from 6.14 to 7.31 after introduction of the electronic weekend medical handover system. As a result, this project has become part of the junior doctors medical induction, ensuring permanence of electronic weekend medical handover. This project takes a step towards improved patient safety as well improving the working conditions for junior doctors in a busy acute medical unit. There is always a need to refine and optimise systems and though this project is not perfect, it is a step toward electronic handover that is available now and free of cost.